Context dependent effects of chimeric peptide morpholino conjugates contribute to dystrophin exon-skipping efficiency - Yin, HF; Boisguerin, P; Moulton, HM; Betts, C; Seow, Y; Boutilier, J; Wang, Q; Walsh, A; Lebleu, B; Wood, MJA (Cell Press, 2016)
We have recently reported that cell-penetrating peptides (CPPs) and novel chimeric peptides containing CPP (referred as B peptide) and muscle-targeting peptide (referred as MSP) motifs significantly improve the systemic exon-skipping activity of morpholino phosphorodiamidate oligomers (PMOs) in dystrophin-deficient mdx mice. In the present study, the general mechanistic significance of the chimeric peptide configuration on the activity and tissue uptake of peptide conjugated PMOs in vivo was investigated. Four additional chimeric peptide-PMO conjugates including newly identified peptide 9 (B-9-PMO and 9-B-PMO) and control peptide 3 (B-3-PMO and 3-B-PMO) were tested in mdx mice. Immunohistochemical staining, RT-PCR and western blot results indicated that B-9-PMO induced significantly higher level of exon skipping and dystrophin restoration than its counterpart (9-B-PMO), further corroborating the notion that the activity of chimeric peptide-PMO conjugates is dependent on relative position of the tissue-targeting peptide motif within the chimeric peptide with respect to PMOs. Subsequent mechanistic studies showed that enhanced cellular uptake of B-MSP-PMO into muscle cells leads to increased exon-skipping activity in comparison with MSP-B-PMO. Surprisingly, further evidence showed that the uptake of chimeric peptide-PMO conjugates of both orientations (B-MSP-PMO and MSP-B-PMO) was ATP- and temperature-dependent and also partially mediated by heparan sulfate proteoglycans (HSPG), indicating that endocytosis is likely the main uptake pathway for both chimeric peptide-PMO conjugates. Collectively, our data demonstrate that peptide orientation in chimeric peptides is an important parameter that determines cellular uptake and activity when conjugated directly to oligonucleotides. These observations provide insight into the design of improved cell targeting compounds for future therapeutics studies.